The The Influence of Visual Media Usage on the Mathematics Learning Outcomes of Al-Munir Islamic Junior High School Students - Juwita Dyah Wulandari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
The purpose of this study is to ascertain how the use of visual aids, such as refusi boards, affects the learning outcomes of mathematics students at Al-Munir Islamic Junior High School when studying Relations and Functions. The study employed a posttest-only control group design and a quasi-experimental research methodology. Two classes made up the research sample: the experimental class, which learned using a refusi board as a visual aid, and the control group, which learned using traditional techniques devoid of visual aids. A post-treatment mathematics learning outcome test was used to collect data. The two groups' learning outcomes differed significantly, as indicated by the Asymp. signature value (2-tailed) of 0.033 (<0.05), which was obtained from data analysis using the Mann-Whitney U test. In comparison to the control class, which had an average rank of 21.14 for student learning outcomes, the experimental class had an average rank of 29.86. These findings suggest that using a refusion board as a visual aid improves students' learning outcomes in mathematics when it comes to Relations and Functions. As a result, this media is suggested as a different but equally effective learning method for enhancing comprehension of mathematical ideas.